2012
DOI: 10.18097/pbmc20125801043
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and Thermodynamic Analysis of Dimerization Inhibitors Binding to HIV Protease Monomers by Surface Plasmon Resonance

Abstract: Here, we describe the analysis of kinetic and thermodynamic parameters for binding of peptide and nonpeptide dimerization inhibitors to immobilized HIV protease (HIVp) monomers by using surface plasmon resonance. Molecular interactions were investigated at different inhibitors concentrations (0-80 μM) and temperatures (15-35°C). The kinetic, equilibrium and thermodynamic parameters have been determined. It was found that both inhibitors were characterized by similar interaction parameters. The complex formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 19 publications
2
13
0
Order By: Relevance
“…The low level of ADR binding in the Fc4 channel with the FECH dimers could be explained by contaminations with FECH monomers in the channel. The presence of small amounts of monomers after the chemical stabilization of the dimeric form of other proteins was also noted earlier [ 15 , 16 ].…”
Section: Resultssupporting
confidence: 72%
“…The low level of ADR binding in the Fc4 channel with the FECH dimers could be explained by contaminations with FECH monomers in the channel. The presence of small amounts of monomers after the chemical stabilization of the dimeric form of other proteins was also noted earlier [ 15 , 16 ].…”
Section: Resultssupporting
confidence: 72%
“…The immobilized HIVp was subsequently monomerized by long term washing with the running buffer; this procedure was accompa nied by gradual dissociation of HIVp dimers [18].…”
Section: Kinetic and Thermodynamic Analysis Of Dimerization Inhibitorsmentioning
confidence: 99%
“…In our previous study by using bioinformatic methods we predicted several small organic com pounds, which could bind at the interface of HIVp dimerization. Subsequent SPR based biosensoric screening in the monomer dimer test system showed that one potential nonpeptide inhibitor (NPI) of HIVp dimerization (compound NCS 134382, NCI data base) selectively interacted only with the HIVp mono mer and inhibited HIVp enzymatic activity in vitro with the IC 50 value of about 10 -6 M [17,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has become increasingly apparent that kinetic properties-especially dissociation rate constant (k off ) or drug-target residence time (τ)-are more important for drug potency and are gradually being used in real-world lead optimization and drug design [1][2][3][4][5]. At present, kinetic properties are mainly determined by laboratory techniques, such as capillary electrophoresis, [6] affinity chromatography [7] and surface plasmon resonance methods [8,9], etc. However, there are still many technical difficulties need to be addressed, e.g., more time consumed, high cost and large measurement errors, which limit drug R&D to a large degree.…”
Section: Introductionmentioning
confidence: 99%